POLITICAL FANDOMS AND SUPERPARTICIPANTS IN POLITICAL CONVERSATIONS ON TWITTERTwitter, social network analysis, political polarization, fandoms - Zago, Gabriela; Recuero, Raquel; Soares, Felipe (AoIR Selected Papers of Internet Research, 2018)
In this proposal, we discuss the role of superparticipants in political conversations on Twitter. Our hypothesis is that these highly active users show a clear political position and intentionally act to give visibility to some topics and to reduce the visibility of others, practices that are similar to those observed among fans in popular culture. In terms of methods, we use social network analysis metrics to identify the modularity of the network and users that receive more attention than others (higher indegree) or mention more other users (higher outdegree). We collected tweets related to the impeachment of the Brazilian ex-president Dilma Rousseff in 2016 in three critical dates of the process. By observing the users with higher outdegree in each network, we noticed some patterns and behaviors that can characterize those users as political fans. Our main finding is that the superparticipants with higher outdegree helped to shape the polarized networks by retweeting like-minded accounts, and thus are important and influence the study of polarized political networks on Twitter.